Preschool Parent's Health Education Improving Family Role Model of Fruit Vegetable Consumption - Rohayati Rohayati; Etty Rekawati; Poppy Fitriani (poltekkes kemenkes mataram, 2021)
Prevention of obesity should start early because obesity in children can continue into adulthood. Consumption of vegetables and fruit according to the recommendations is proven to prevent obesity from an early age. The role model of parents is very important in shaping the behavior of eating fruits and vegetables in preschool children. The aim of study to determine the effect of online and face-to-face health education methods on the role models of parents in consuming fruits and vegetables. The study used a quasi-experimental design pre-post-test without a control group. The number of samples was 115 parents of students spread across 5 kindergarten schools. The results showed 49.6% of parents have graduated from high school with an income of 52.7% above the minimum wage. The results of statistical tests showed that there was an effect of online and face-to-face health education methods on the role models of parents in eating vegetables and fruit with their children (17.92 ± 4.61, p = 0.00, 95% CI). Health education using online and face-to-face methods can be an intervention in increasing parental role models of fruit and vegetable consumption.